If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3d-13=11-3d
We move all terms to the left:
3d-13-(11-3d)=0
We add all the numbers together, and all the variables
3d-(-3d+11)-13=0
We get rid of parentheses
3d+3d-11-13=0
We add all the numbers together, and all the variables
6d-24=0
We move all terms containing d to the left, all other terms to the right
6d=24
d=24/6
d=4
| 3^x+1+3^3=108 | | 7+x/2=9 | | 10u+83=2u+91 | | x+0.6=1.05+1.1x | | Y=⅔x+2 | | 3=z/5-2 | | 4u-11=u+7 | | 5/3(2x+7)=5 | | 08.t=24 | | x-53=-6 | | 5/3(2x+7=5 | | 5(4x–1.5x)+12=4x–5 | | f-77/3=7 | | r−18.5=−4.8 | | 7f-6=22 | | 2x=3x-7x | | 3=c/4-3 | | t/9+45=52 | | 1,250-27.50w=1,400-20w | | 88=5v+13 | | 5=9w=23 | | 64=16u= | | 88=5v+14 | | x4=310 | | 10=c+23/7 | | 2x/5+10=22 | | -4(2x–3)=6(x+5)–20 | | 80=8(t−84) | | 40y=40 | | 13=a+18 | | 48-6y/3=0 | | 2b=-33 |